(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article analyzes the organizational and economic mechanisms, institutional factors, and efficiency conditions for attracting foreign investments into the national economy. It highlights international experience, global economic trends, and priority directions for shaping the investment environment in the case of Uzbekistan. Furthermore, the role of legal guarantees, infrastructure development, tax policy, and the effectiveness of public administration in enhancing investment attractiveness is scientifically substantiated. The author provides recommendations on the importance of strategic planning and institutional stability in the process of attracting investments.